2017
DOI: 10.1002/jcp.26189
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stiffness regulated migration and angiogenesis potential of A549 cells and HUVECs

Abstract: Tumor tissue tends to stiffen during solid tumor progression. Substrate stiffness is known to alter cell behaviors, such as proliferation and migration, during which angiogenesis is requisite. Mono- and co-culture systems of lung cancer cell line A549 and human umbilical vein endothelial cells (HUVECs), on polydimethylsiloxane substrates (PDMS) with varying stiffness, were used for investigating the effects of substrate stiffness on the migration and angiogenesis of lung cancer. The expressions of matrix metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…MMP‐2 proteins were high expressed at the early stage of A549 cells, so the targeting ability of as‐prepared NCs could be assessed with these cells test. As shown in Figure , the morphology of some A549 cells were changed when cells were cultured with pure NCs; moreover, the images in Figures and indicate that some cells became loose and smaller (marked by white arrows in Figure ) when treated by Cur‐NCs, CTX‐NCs and CTX‐NCs‐Cur for 12 hours, and many cells changed round (marked by white arrows in Figure ) at 36 hours of treatments, which might partly result from the stiffness effect of the prepared NCs . The results of MTT in Figure E‐H indicate that there was no obvious cytotoxicity of 4 NCs on HUVEC cells at their lower concentration (≤100 μg mL –1 ); however, the MTT values at 200 μg mL −1 of the as‐prepared NCs in Figure F,H remarkably decreased ( P < .05).…”
Section: Resultsmentioning
confidence: 95%
“…MMP‐2 proteins were high expressed at the early stage of A549 cells, so the targeting ability of as‐prepared NCs could be assessed with these cells test. As shown in Figure , the morphology of some A549 cells were changed when cells were cultured with pure NCs; moreover, the images in Figures and indicate that some cells became loose and smaller (marked by white arrows in Figure ) when treated by Cur‐NCs, CTX‐NCs and CTX‐NCs‐Cur for 12 hours, and many cells changed round (marked by white arrows in Figure ) at 36 hours of treatments, which might partly result from the stiffness effect of the prepared NCs . The results of MTT in Figure E‐H indicate that there was no obvious cytotoxicity of 4 NCs on HUVEC cells at their lower concentration (≤100 μg mL –1 ); however, the MTT values at 200 μg mL −1 of the as‐prepared NCs in Figure F,H remarkably decreased ( P < .05).…”
Section: Resultsmentioning
confidence: 95%
“…ECs are capable of modulating their behavior in response to alterations in substrate stiffness. For example, HUVECs can increase their expression of MMPs, such as MMP2, MMP3, MMP4, and MMP14, and of angiogenic GF, such as VEGFA, when co-cultured in vitro with adenocarcinoma cells on stiff polydimethylsiloxane (PDMS) substrates, whilst MMPs are downregulated with decreased stiffness (Zhao et al, 2018). Increased stiffness of polyacrylamide (PA) scaffolds from 1 to 10 kPa has been shown to boost the endothelial cell response to VEGF by increasing VEGFR-2 internalisation (LaValley et al, 2017).…”
Section: Mechanical Properties Of the Scaffoldmentioning
confidence: 99%
“…Stiffness, as an important mechanical feature of the matrix, can affect cell morphology, proliferation, migration and differentiation. Studies have shown that the adhesion, proliferation and expression of the proangiogenic-related factors of endothelial cells increase with substrate stiffness [74]. With the increase in substrate stiffness, endothelial cells migrate farther and deposit more linearly and aligned on fibronectin fibres [75,76].…”
Section: Stiffnessmentioning
confidence: 99%